URACHAL CARCINOMA IN BLADDER - 薛丽燕 吕宁 何祖根 林冬梅 刘秀云 (Chinese journal of cancer research, 2004)
Objective: To investigate the clinicopathologic features and diagnostic criteria of urachal carcinoma in the bladder. Methods: Seven cases of urachal carcinoma in the bladder were analyzed retrospectively. Results: All the tumors were found locating in the dome of bladder. Of them, 4 were mucinous adenocarcinoma, one was well differentiated papillary enteric adenocarcinoma, one was well differentiated squamous carcinoma, and one was neuroendocrine carcinoma. Cystomorphous urachal remnants were found in 4 cases. The main complaint was hematuria and all patients underwent partial excision of bladder and urachus. Conclusion: Mucinous adenocarcinoma is the main histo-pathological type, and cystomorphous urachal remnants are often accompanied with urachal carcinoma in the bladder. The key diagnostic criteria of urachal carcinoma in bladder are site and histopathology. And to examine the specimens carefully to fred the urachal remnants is important.